2014
DOI: 10.1111/tmi.12245
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and biochemical reference values of Gambian infants

Abstract: Abstractobjective To establish haematological and biological reference values for Gambian infants. methods Basic haematological and biochemical indices were analysed in blood samples obtained from healthy infants from Sukuta in the Western Division of The Gambia. The 2.5 and the 97.5 centiles for these indices were estimated.results Reference ranges for haematological and biochemical indices were determined. Haemoglobin, total white cell count (WBC) and platelet levels decreased with age (P < 0.001), whereas m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Several African studies that have shown lower red blood cell indices in children and adults [16, 24, 25, 43] compared to American or European children [37]; we also observed this for Hb, Hct and MCV(Table 5 and S4 Table). This may be attributed to several factors that are common in the community, including malaria, other parasitic infestations [44, 45], haemoglobinopathies [46] and iron deficiency anaemia [47].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Several African studies that have shown lower red blood cell indices in children and adults [16, 24, 25, 43] compared to American or European children [37]; we also observed this for Hb, Hct and MCV(Table 5 and S4 Table). This may be attributed to several factors that are common in the community, including malaria, other parasitic infestations [44, 45], haemoglobinopathies [46] and iron deficiency anaemia [47].…”
Section: Discussionsupporting
confidence: 85%
“…Creatinine and transaminases are generally comparable to that of Caucasians [16, 23, 24]. Similarly, studies in African children have typically shown that red blood cell parameters such as haemoglobin, haematocrit and mean corpuscular volume are lower than those of Caucasians, with the exception of platelets [25, 26] and eosinophils, which tend to be higher, the latter being attributed to helminth infestation.…”
Section: Introductionmentioning
confidence: 94%
“…When compared to reference intervals generated for infants, we observe that the reference intervals for haemoglobin, WBC T and differentials are comparable; the main difference being that those from this study but with slightly lower limits and wider range of values compared to infants and data from western countries compared in the paper [ 19 ]. The consistency of the data is also seen when compared to reference intervals for older children and adults which also showed similar trends for WBCs and haemoglobin and no association with gender [ 20 ].…”
Section: Discussionmentioning
confidence: 67%
“…Trends of age-specific differences in some parameters were also evident although this needs further verification in larger cohorts (Table 6). At present there are few reports available for adolescents and younger age groups, especially on biochemistry analytes in Africa [11,19,31,32]. …”
Section: Discussionmentioning
confidence: 99%